The Impact of Macro Economic Variables on the Exchange Rate of Large Ruminant Livestock Farmers in East Nusa Tenggara: An Analysis of the Time Series 2008-2022 - johny agustinus koylal; Stefanus M. Kuang; Jamseng C. Abineno (Jurnal Penelitian Pertanian Terapan, 2024)
This study aims to examine the effects of inflation, loan interest rates, labor, and exchange rates on the exchange rate of large ruminant cattle farmers in East Nusa Tenggara and the development of the exchange rate achievement rate of large ruminant cattle farmers for the period 2008-2022. The data used in this study is time series data for the period 2008-2022 obtained from the Central Statistics Agency. The analysis method used is a multiple regression model with software econometric views 12 and a quantitative descriptive method. The research variables include the exchange rate of large ruminant farmers, inflation, loan interest rates, labor, and exchange rates. The results of the analysis show that inflation, loan interest rates, and exchange rates have a significant effect on the exchange rate of large ruminant farmers. The purchasing power and welfare of East Nusa Tenggara farmers are relatively low nationally but have a higher average growth.